Penerapan Algoritma Dijkstra dan Algoritma Bellman-Ford untuk Menentukan Rute Terpendek - Dhea Ayu Devi Mayang Sari; Granita; Dinda Handayani (Mathematics Study Program, Faculty of Mathematics and Natural Science, Universitas Negeri Jakarta, 2024)
Siak Sri Indrapura is a regency located in Riau Province. Siak Regency is expected to become a tourist destination capable of attracting visits from both domestic and foreign tourists. For travelers who are visiting Siak Palace For those experiencing it for the initial time, of course they will have difficulty determining the direction of the road, so tourists use alternative technology such as Google Maps to determine their direction of travel. In Google Maps there are various travel routes, to save time tourists will defi-nitely choose the shortest travel route. To determine the shortest route, of course, re-quires calculations to avoid mistakes. In this research, the shortest route from Pek-anbaru to Siak Palace was carried out using The algorithms of Dijkstra and Bellman-Ford. This algorithm was chosen because it can help calculate the shortest route that tourists can take. It was found that in the last iteration The Dijkstra algorithm and the Bellman-Ford algorithm, both of which travel route from Pekanbaru to Siak Palace was 125.1 km with a node route (Jalan Raya Pekan – Jalan SM Amin – Jalan Raya Panjang Okura – Jalan Perawang Siak – Jalan Buatan – Siak).